Concept of global peace: military, terrorist and informational threats - Vitalii Dankevych; Vitaliy B. Kovalchuk; Bogdana B. Melnychenko; Yaryna S. Bohiv; Nataliia D. Slotvinska (Revista Guillermo de Ockham, 2023)
The article deals with the analysis of transformational processes of the doctrinal and praxeological interpretation of the concept of global peace in the context of overcoming modern military, terrorist and informational threats. The tasks solved in the article are: the essence of understanding of the modern concept of global peace is revealed; the effectiveness of the mechanism of international institutions in providing counteraction to the military threat is analyzed; terrorism as an opposition to peace and stability is studied; the nature of the challenges to the information and educational environment as a significant factor in ensuring global peace is revealed. The humanistic approach is distinguished as one that has a special axiological value for research, with a methodological triad of methods used being philosophical, general scientific, and special scientific methods. The elements of the concept of the global world order are the functioning of international and national subjects to ensure peace and development of civil society, including the education of the global world order, tolerance, democratic values of constitutionalism and the rule of law, and other primary legal axiological values. The originality of the research lies in the comprehensive analysis of globalization threats to the concept of peace and security of the international society in the military, anti-terrorist and information spheres with the demonstration of empirical material from the Russian-Ukrainian war in 2022.